The effectiveness of group dialectical behavior therapy on increasing emotional, communicative, sexual and social-recreational intimacy of depressed couples - Fariba Kiani; Mosa Amiryan Farsani; Shahrban Mehrabi (University of Hormozgan, 2023)
Marital issues and depression commonly manifest within couples, displaying a reciprocal connection. This research aimed to assess the impact of group-based dialectical behavior therapy on enhancing emotional, communicative, sexual, and social-recreational intimacy among couples experiencing depression. Conducted as an experimental study with both experimental and control groups, the research involved 20 couples seeking assistance at counseling centers in Shahrekord (Iran) due to depression. The couples were selected through purposive sampling and then randomly assigned to either the experimental or control group. Utilizing a marital intimacy questionnaire, baseline measurements of marital intimacy were taken for both groups prior to the intervention (pre-test). Following an 11-week intervention comprising 90-minute sessions for the experimental group, post-intervention assessments were conducted for both groups using the same questionnaire (post-test). The data underwent analysis involving descriptive statistics and Multivariate Covariance method. The results indicated that dialectical behavior therapy yielded significant enhancements in emotional, communicative, sexual, and social-recreational intimacy for depressed couples within the experimental group, compared to the control group (P<0.05). The study underscores the meaningful implications of exploring the efficacy of dialectical behavior therapy on various dimensions of intimacy for couples experiencing depression, offering valuable insights into the mental well-being of such couples.